Bulk Sales Laws: Businesses Included - Frank William Miller (Washington University Law Quarterly, 1954)
It is important to keep uppermost in mind the fact that this analysis is of necessity concerned with the effect of the superimposition of a statutory scheme on the common law. Thus attention must first be directed to the statutory construction aspects of the problem, and more particularly to the part, if any, played by the so-called canons of statutory interpretation.
Keywords: Sales